Development of hybrid friction stir welding and adhesive bonding single lap joints in aluminium alloys - Ricardo Leite Maciel; Virginia Infante; Daniel Braga; Pedro Moreira; Tiago Bento; Lucas da Silva (Fracture and Structural Integrity)
Aircraft have been manufactured for decades using a wide variety of welding and joining techniques. There have been signiﬁcant developments in techniques over the last 15–20 years.